SEMANTIC AND WORD MEANING: THE STUDY OF POLYSEMOUS WORDS IN ENGLISH (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This paper explores the phenomenon of polysemy in the English language, focusing on the multiple meanings of words and their semantic implications. Polysemy, the coexistence of many possible meanings for a word or phrase, is a fundamental aspect of linguistic studies. This research delves into the theoretical frameworks that explain polysemy, analyzes examples from the English language, and discusses the challenges and implications for language learners and linguists.